PAHs in decaying Quercus ilex leaf litter: Mutual effects on litter decomposition and PAH dynamics (Chemosphere, 2014)
The investigation of the relationships between litter decomposition and polycyclic aromatic hydrocarbons (PAHs) is important to shed light not only on the effects of these pollutants on fundamental ecosystem processes, such as litter decomposition, but also on the degradation of these pollutants by soil microbial community. This allows to understand the effect of atmospheric PAH contamination on soil PAH content via litterfall. At this aim, we studied mass and PAH dynamics of Quercus ilex leaf litters collected from urban, industrial and remote sites, incubated in mesocosms under controlled conditions for 361d. The results highlighted a litter decomposition rate of leaves sampled in urban>industrial>remote sites; the faster decomposition of litter of the urban site is also related to the low C/N ratio of the leaves. The PAHs showed concentrations at the beginning of the incubation of 887, 650 and 143ngg−1d.w., respectively in leaf litters from urban, industrial and remote sites. The PAHs in litter decreased along the time, with the same trend observed for mass litter, showing the highest decrease at 361d for the urban leaf litter. Anyway, PAH dynamics in all the litters exhibited two phases of loss, separated by a PAH increase observed at 246d and mainly linked to benzo[e]pyrene.

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.